Efficacy of Air and Oxygen Micro-nano Bubble Waters Against Colletotrichum gloeosporioides and Impacts on Postharvest Quality of ‘Fan Retief’ Guava Fruit - Harold K. Malahlela; Zinash A. Belay; Rebogile R. Mphahlele; Oluwafemi James Caleb (Journal of Food Protection)
This study focused on the application of micro-nano bubbles (MNBs) water generated using air or oxygen (O2), as an alternative to chlorine-based wash for fruits. For the in vitro and in vivo investigation, 106 spore or conidia/mL Colletotrichum gloeosporioides suspension was used, and treated with solutions of air- or O2-MNB for 30- or 60-min, sodium hypochlorite (NaOCl), and untreated (as control). In the second experiment, freshly harvested guava fruits were washed with tap water (control), NaOCl (standard practice), air-, or O2-MNB (for 15- or 30-min). All samples were packaged, stored for 21 days at 13 °C, and monitored for changes in natural microbial population and quality attributes. Based on the confocal laser and transmission electron microscopy results, exposure of C. gloeosporioides to air-MNB for 60 min resulted in the lowest viable cell count (%) compared to control and other treatments (O2-MNB and NaOCl). Air- and O2-MNB treatments damaged cellular structures, disrupted cell membrane integrity, and deformed hyphal morphology. Washing ‘Fan Retief’ guava (Psidium guajava L.) in air- or O2-MNB (for 15 and/or 30 min), better-retained tissue strength, delayed changes in color, and total soluble solid (TSS) content. Notably, MNB treatments were as effective as NaOCl washing and significantly reduced microbial load on fruit surface by ≥2 Log (p < 0.05). Micro-nano bubble water treatment offers a new paradigm for decontamination and preservation of guava fruit quality.